On Gamma-Ideals, Gamma-Submonoids and Isomorphism Theorems of Gamma-Monoids via Gamma-Submonoids (European Journal of Pure and Applied Mathematics, 2023)
This study introduces the concept of Gamma-ideals and Gamma-submonoids of Gamma-monoids and investigates their relationships with the existing Gamma-order-ideals. Moreover, quotient of Gamma-monoids and isomorphism theorems via Gamma-submonoids are proved.
Keywords: Gamma-monoids; Homomorphism; Isomorphism Theorems